Malay-Muslim Educational Institutions In South Thailand (1930s-1990s) - Hayimasae, Numan (2010)

(untitled)
The study investigates the development of institutions under the madrasah pattern and other institutions established on the basis of madrasah system from the 1930s until 1990s. Madrasahs in the South of Thailand were influenced by madrasahs of the Haramayn which had developed since the late 19th century. However, the first generation madrasahs (1930s-1940s) could not last long due to government pressures. The development of madrasah in Bangkok and nearby provinces had begun earlier in the 1910s. They expanded in the following decades to follow closely the government policies while some of them were taken over by the government.